Classification and determinants of passing difficulty in soccer: a multivariate approach - Merlin, M.; Pinto, A.; Gomes de Almeida, A.; Moura, F. A.; Da Silva Torres, R.; Cunha, S. A. (Science and Medicine in Football, 2022)
Introduction: Usually, the players` or teams` efficiency to perform passes is measured in terms of accuracy. The degree of difficulty of this action has been overlooked in the literature. Objectives: The present study aimed to classify the degree of passing difficulty in soccer matches and to identify and to discuss the variables that most explain the passing difficulty using spatiotemporal data. Results: The data used corresponds to 2,856 passes and 32 independent variables. The Fisher Discriminant Analysis presented 72.0% of the original grouped cases classified correctly. The passes analyzed were classified as low (56.5%), medium (22.6%), and high difficulty (20.9%), and we identified 16 variables that best explain the degree of passing difficulty related to the passing receiver, ball trajectory, pitch position and passing player. Conclusions: The merit and ability of the player to perform passes with high difficulty should be valued and can be used to rank the best players and teams.In addition, the highlighted variables should be looked carefully by coaches when analyzing profiles, strengths and weaknesses of players and teams, and talent identification context. Practical Implications: The values found for each variable can be used as a reference for planning training, such as small side games, and in future research.